AKULTURASI DAN ASIMILASI DALAM KONTEKS INTERAKSI ANTAR ETNIK - Romli, Khomsahrial (Universitas Islam Negeri Raden Intan Lampung, 2015)
Acculturation and assimilation are two very importantconcepts in sociology and anthropology that describecross cultural effects on both minorities as well asmajorities in societies that are multi ethnic and multicultural in nature. There are two different views aboutthe tendencies of acculturation and asimiliasi in thecontext of inter-ethnic interaction. Two trends thatview is constructed two models of ethnic identity,ethnic Exclusive and Inclusive. Exclusive assessethnicity as ethnic tribes should be given priority,assess ethnic inclusive as a rival, and that sometimes,hampering the progress of ethnic for acculturation andassimilation. Because of exclusive ethnic tend to keepa distance, on the contrary, the inclusive one judgehimself has an equal position to the other.